Development of a Waste Plastic-to-Fuel Conversion System for Sustainable Energy Generation in Urban Nigeria - Unegbu, Hyginus; YAWAS, Danjuma (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2025)
Plastic waste pollution has emerged as a critical environmental and public health concern in Nigeria’s rapidly urbanising regions, where improper disposal and inefficient waste management systems persist. In parallel, the country faces acute energy insecurity, largely driven by erratic diesel supply and rising fossil fuel costs. This study presents the design, optimisation, and techno-environmental evaluation of a decentralised pyrolysis-based conversion system for transforming plastic waste into liquid fuel. Polypropylene (PP), high-density polyethylene (HDPE), low-density polyethylene (LDPE), and polystyrene (PS) were thermally degraded at controlled temperatures between 350°C and 500°C under inert conditions. Experimental trials revealed that oil yield increased with temperature, peaking at 450°C for all polymers. PP demonstrated the highest yield (65.1%) followed by PS (63.0%), HDPE (62.5%), and LDPE (60.4%). Fuel characterisation showed calorific values of up to 42.7 MJ/kg and physicochemical properties within acceptable diesel standards. Emissions analysis using flue gas monitoring confirmed low outputs of CO, NOx, and SO₂, all within Euro VI regulatory limits. Energy efficiency was highest for PP-derived fuel at 71.4%. Techno-economic modelling, based on a 10-year operational horizon, produced a net present value of ₦11.8 million, an internal rate of return of 28.4%, and a break-even fuel price of ₦290/litre. Statistical modelling further validated temperature and polymer type as primary determinants of yield performance. The findings demonstrate that decentralised plastic pyrolysis systems can simultaneously address urban waste accumulation, reduce environmental emissions, and provide affordable alternative fuels, making them suitable for integration into Nigeria’s circular economy and energy access strategies.